2017
DOI: 10.5194/hess-21-5547-2017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and modelling of a 9.3 kyr palaeoflood record: correlations, clustering, and cycles

Abstract: Abstract. In this paper, we present a unique 9.5 m palaeolacustrine record of 771 palaeofloods which occurred over a period of 9.3 kyr in the Piànico-Sèllere Basin (southern Alps) during an interglacial period in the Pleistocene (sometime from 780 to 393 ka) and analyse its correlation, clustering, and cyclicity properties. We first examine correlations, by applying power-spectral analysis and detrended fluctuation analysis (DFA) to a time series of the number of floods per decade, and find weak long-range per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…3). Similarly, other high-resolution palaeo-hydrological records (e.g., Witt et al, 2017) and modern observations (e.g., Metzger et al, 2020) have demonstrated non-uniform and non-Poissonian flood frequencies. In addition, the clusters observed during lakelevel fall are characterized by flood frequencies similar to those appearing in the background episodes during lakelevel rise (Figs.…”
Section: Clusters and Regime Transitionsmentioning
confidence: 66%
See 1 more Smart Citation
“…3). Similarly, other high-resolution palaeo-hydrological records (e.g., Witt et al, 2017) and modern observations (e.g., Metzger et al, 2020) have demonstrated non-uniform and non-Poissonian flood frequencies. In addition, the clusters observed during lakelevel fall are characterized by flood frequencies similar to those appearing in the background episodes during lakelevel rise (Figs.…”
Section: Clusters and Regime Transitionsmentioning
confidence: 66%
“…Furthermore, the impacts of climate change on short-term phenomena such as individual storms and floods, which have substantial influence on the in situ water cycle in the Mediterranean Sea, are harder to determine from the available short historical records because the extent of available data does not adequately capture the full diversity of possible hydroclimatic states (e.g., Greenbaum et al, 2010;Tarolli et al, 2012;Metzger et al, 2020). Because palaeohydrologic archives often record centennial and millennial intervals at various resolutions (e.g., Allen et al, 2020;Baker, 2008;Brauer et al, 2008;Redmond et al, 2002;Witt et al, 2017), they have the potential to improve our understating of how climate change is manifested locally as short-term hydroclimatic variability (e.g., Ahlborn et al, 2018;Swierczynski et al, 2012). Nevertheless, this requires continuous high-resolution archives, which are rare, especially in subtropical terrestrial environments (e.g., Zolitschka et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Dulski et al, 2015; Kämpf et al, 2019; Lapointe et al, 2012; Schlolaut et al, 2014; Støren et al, 2010). When these layers are constrained within laminated lacustrine sediments that provide a detailed chronology, it becomes possible to construct time series of events that reveal their frequency and clustering, and sometimes even relative magnitudes (Czymzik et al, 2010; Witt et al, 2017).…”
Section: Advances In Research Methods and Techniquesmentioning
confidence: 99%
“…Such frequency changes and non‐stationarity occurred under different climatic conditions (Brauer et al, 2008; Corella et al, 2016, 2021; Swierczynski et al, 2013), as observed in modern records (Blöschl et al, 2020; Redmond et al, 2002). An increasingly large number of studies indicate that, over centennial time scales, non‐stationarity characterizes both the mean and the variance of flood series, thus forming decadal to centennial clusters of increased flood frequency that stem directly from hydroclimatic variability (Ben Dor et al, 2018; Chiverrell et al, 2019; Czymzik et al, 2010; Witt et al, 2017).…”
Section: Advances In Research Methods and Techniquesmentioning
confidence: 99%
See 1 more Smart Citation